Cases of Pedagogical Discontentment of Secondary English Teachers - Balmeo, Bryan Jester S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This research aimed to analyze secondary English teachers' pedagogical discontent and identify factors relating to this construct. Further, this study established the teachers’ affective response to his evaluation of the effectiveness of his existing teaching practices and goals. This study utilized descriptive research with a qualitative approach using the multiple-case study design. The researcher distributed a pedagogical discontentment checklist to identify the English teachers with ‘high’ or ‘very high’ pedagogical discontentment, wherein eight (8) participants were identified. They belong to the eight (8) secondary schools in one of the districts in the Schools Division of Zambales. The eight (8) participants were subjected to individual interviews and focus group discussions. It was found out that most of the participants were female, middle adult, holding Teacher I position; Seven (7) participants have high pedagogical discontentment whereas only one (1) participant has very high discontentment; Teachers are recommended to undergo training workshops on pedagogy. Conducting regular focus group discussions on improving the weak areas are noted; An investigation on the frustrations, attitudes and beliefs, interventions, classroom practices, and aspirations of the English teachers should be conducted considering their contexts. Professional learning communities are deemed necessary.